Smart textile lighting/display system with multifunctional fibre devices for large scale smart home and IoT applications - Hyung Woo Choi; Dong-Wook Shin; Jiajie Yang; Sanghyo Lee; Cátia Figueiredo; Stefano Sinopoli; Kay Ullrich; Petar Jovančić; Alessio Marrani; Roberto Momentè; João Gomes; Rita Branquinho; et al. (Nature Communications, 2022)
A large scale approach for multifunctional smart display systems in traditional textiles has yet to be demonstrated. Here, authors present a foldable, rollable 46-inch smart textile lighting/display system for smart homes and internet of things applications via the systematic design and integration of versatile fibre devices into textile form factors.